2020
DOI: 10.1108/jhlscm-01-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Lean readiness assessment model – a tool for Humanitarian Organizations' social and economic sustainability

Abstract: Purposepurpose of this study is to present a Lean Readiness Assessment Model (LRAM) for assessing the readiness of Humanitarian Organizations (HO) for adopting Lean Management (LM) (Johanson et al.) practices. Literature reveals that implementation of LM itself is a cost and most organizations have failed to adopt LM techniques due to a non-readiness status and a non-supportive organizational culture. This situation indicates that the assessment of organizations' readiness before implementation of lean techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 83 publications
5
41
0
Order By: Relevance
“…Human resource management skills are considered important and it was found that there is a positive relationship between the skills researched and humanitarian logistical performance Rajakaruna et al (2017) This research focused on identifying the skills of humanitarian logisticians in Sri Lanka. It was found that skills related to HRM are highly important for humanitarian logistics management Shafiq and Soratana (2020) This paper presented a lean model to assess the readiness of humanitarian organizations for adopting lean management. It was found that HRM factors such as the availability of skilled workers, workforce empowerment and investment of funds for training are important to implement lean practices in HSC Sharifi-Sedeh et al (2020) This study explored factors behind the pre-positioning of relief items (PRI).…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…Human resource management skills are considered important and it was found that there is a positive relationship between the skills researched and humanitarian logistical performance Rajakaruna et al (2017) This research focused on identifying the skills of humanitarian logisticians in Sri Lanka. It was found that skills related to HRM are highly important for humanitarian logistics management Shafiq and Soratana (2020) This paper presented a lean model to assess the readiness of humanitarian organizations for adopting lean management. It was found that HRM factors such as the availability of skilled workers, workforce empowerment and investment of funds for training are important to implement lean practices in HSC Sharifi-Sedeh et al (2020) This study explored factors behind the pre-positioning of relief items (PRI).…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…The use of the non-parametric statistical method PLS-SEM in academic research has continued to increase since the 1990s [68]. PLS-SEM has been specifically used in investigations on economic sustainability [69][70][71], social sustainability [69,70] and environmental sustainability [69,70] in the context of organizations. In addition, it is common to use this methodology in studies on management [68,72], marketing [73][74][75][76] and tourism [77,78].There is analysis implementing this statistical method (PLS-SEM) in the context of tourist destinations [79], hotel management [80][81][82] and eWOM generation [3,45].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, previous studies have developed and implemented different methods and tools, e.g., assessment tools [74][75][76], identification approaches [46,66,[77][78][79], classification methods [80][81][82], etc., to investigate the CSFs of a construction project. Other studies identified the CSFs of construction projects by the certain construction project delivery methods (PDM) which determine each stage in the life cycle, including design, construction and maintenance and required a clear definition of responsibilities of each project participant [14,46].…”
Section: Literature Reviewmentioning
confidence: 99%